2009
DOI: 10.1371/journal.pone.0006412
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Analysis of Immune Infiltrates in High-Grade Serous Ovarian Cancer Reveals CD20, FoxP3 and TIA-1 as Positive Prognostic Factors

Abstract: BackgroundTumor-infiltrating T cells are associated with survival in epithelial ovarian cancer (EOC), but their functional status is poorly understood, especially relative to the different risk categories and histological subtypes of EOC.Methodology/Principal FindingsTissue microarrays containing high-grade serous, endometrioid, mucinous and clear cell tumors were analyzed immunohistochemically for the presence of lymphocytes, dendritic cells, neutrophils, macrophages, MHC class I and II, and various markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
349
5
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 387 publications
(383 citation statements)
references
References 126 publications
21
349
5
8
Order By: Relevance
“…1 In support of this, the accumulation of tumor-infiltrating lymphocytes significantly correlate with increased survival in HGSC patients. 1 Additionally, recent early phase clinical trials have reported clinical activity (including complete responses) in some patients with HGSC in response to PD-1/PD-L1 blockade.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…1 In support of this, the accumulation of tumor-infiltrating lymphocytes significantly correlate with increased survival in HGSC patients. 1 Additionally, recent early phase clinical trials have reported clinical activity (including complete responses) in some patients with HGSC in response to PD-1/PD-L1 blockade.…”
mentioning
confidence: 76%
“…1 In support of this, the accumulation of tumor-infiltrating lymphocytes significantly correlate with increased survival in HGSC patients. 1 Additionally, recent early phase clinical trials have reported clinical activity (including complete responses) in some patients with HGSC in response to PD-1/PD-L1 blockade. Notwithstanding some encouraging clinical responses following monotherapy with ICI, the presence of multiple non-redundant immunosuppressive mechanisms will likely contribute to resistance or lack of activity for many patients.…”
mentioning
confidence: 76%
“…These markers were not associated with improved outcomes in our relatively small cohort of highgrade serous carcinomas but other series with greater case numbers have consistently demonstrated immune cell infiltrates to be a favorable prognostic factor. 18,19,22,24,59 TP53 abnormalities (loss of expression, which correlates with nonsense mutations or deletions, or overexpression, which correlates with missense mutations) were essentially ubiquitous in high-grade serous cancers with BRCA1 or BRCA2 abnormalities and also were associated with favorable outcome. Thus BRCA mutations, immune cell infiltrates, and TP53 abnormalities co-vary in high-grade serous carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Tumors from women with high-grade serous cancers frequently show a host immune response, and the presence of cytotoxic T lymphocytes, and T-regulatory cells is consistently associated with favorable prognosis. [18][19][20][21][22][23][24] Germline mutations in BRCA1 and BRCA2 are present in B18% of ovarian cancer patients with high-grade serous carcinoma. [25][26][27] When combined with BRCA deficiencies that result from somatic mutations or epigenetic silencing, it appears that up to half of all high-grade serous ovarian cancers (hereditary and sporadic) have BRCA dysfunction.…”
mentioning
confidence: 99%
“…Moreover, TIL are often abundant in late-stage tumors yet have obviously failed to prevent tumor progression (15)(16)(17)(18)(19). Together, these features suggest that TIL in ovarian cancer may have experienced prolonged exposure to their cognate antigen and, as a consequence, may be functionally exhausted.…”
Section: Introductionmentioning
confidence: 99%